2021
DOI: 10.1038/s41598-021-00473-6
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis in badgers where the bovine tuberculosis epidemic is expanding in cattle in England

Abstract: Bovine tuberculosis (bTB) is an important animal health and economic problem for the cattle industry and a potential zoonotic threat. Wild badgers (Meles meles) play a role on its epidemiology in some areas of high prevalence in cattle, particularly in the UK and Republic of Ireland and increasingly in parts of mainland Europe. However, little is known about the involvement of badgers in areas on the spatial edge of the cattle epidemic, where increasing prevalence in cattle is seen. Here we report the findings… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…The prevalence of TB within our study population was low in absolute terms (44 of 269 badgers = 16.4%) and compared to a previous study in Ireland (43.2%) ( Corner et al, 2012a ), but relatively high compared to randomly sampled badger populations across the UK (Wales – 7.3% ( Schroeder et al, 2021 ); England – 8.3% ( Swift et al, 2021 )). These differences reflect the reactive nature of the badger trapping which provided both us and Corner et al (2012) with samples, i.e.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The prevalence of TB within our study population was low in absolute terms (44 of 269 badgers = 16.4%) and compared to a previous study in Ireland (43.2%) ( Corner et al, 2012a ), but relatively high compared to randomly sampled badger populations across the UK (Wales – 7.3% ( Schroeder et al, 2021 ); England – 8.3% ( Swift et al, 2021 )). These differences reflect the reactive nature of the badger trapping which provided both us and Corner et al (2012) with samples, i.e.…”
Section: Discussioncontrasting
confidence: 73%
“…These differences reflect the reactive nature of the badger trapping which provided both us and Corner et al (2012) with samples, i.e. the badgers were targeted in areas which were experiencing TB outbreaks (cf High TB Area East – 18.6% ( Schroeder et al, 2021 ); highest county density – 15% ( Swift et al, 2021 )). The frequency distribution of Strongyloides spp.…”
Section: Discussionmentioning
confidence: 96%
“…The study was designed to detect an incidence rate of 5 % based on our previous studies of alphacoronaviruses in British rodents [55] with a target of 73 samples per species calculated with the online Epitools sample size calculator [56]. For some species including otters and badgers, for which there were ongoing post-mortem studies of found dead (largely road kill) animals [57][58][59][60], this sample size target was readily achieved. This target was also achieved for water voles facilitated by a network of wildlife monitoring and captive breeding for re-introduction [61].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cows might go through periods of immunosuppression during lactation, leading to an increased susceptibility to infection. Moreover, females are typically more sociable than males and can interact more easily with other animals, raising the risk of disease transmission [ 50 ]. However, Borham et al [ 48 ] and Ullah et al [ 51 ] reported that there was a significantly higher risk for males to develop bTB lesions.…”
Section: Discussionmentioning
confidence: 99%